2012
DOI: 10.1007/s00227-012-1917-6
|View full text |Cite
|
Sign up to set email alerts
|

Mating system of the burrowing crab Neohelice granulata (Brachyura: Varunidae) in two contrasting environments: effect of burrow architecture

Abstract: Few studies conducted in crustaceans have demonstrated how habitat features could shape the mating systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 41 publications
3
49
0
2
Order By: Relevance
“…Those studies demonstrated that the reproductive season is longer in MCL than in SAO, extending from September to February and from November to January, respectively, although the differences in the reproductive traits were not associated with a latitudinal temperature gradient; instead, the quality and quantity of benthic food resources and productivity may be responsible for the observed reproductive differences (Ituarte et al 2006;Bas et al 2007). Further, recent studies have demonstrated that burrows are places used for copulation, although differences in the form and size of the burrows between the two habitats promote differences in successful post-copulatory guarding behavior (Sal Moyano et al 2012). During the reproductive season, N. granulata individuals can spawn several batches of eggs (Ituarte et al 2004(Ituarte et al , 2006, although the extent of the receptive period was not assessed before the present study.…”
Section: Introductionmentioning
confidence: 96%
“…Those studies demonstrated that the reproductive season is longer in MCL than in SAO, extending from September to February and from November to January, respectively, although the differences in the reproductive traits were not associated with a latitudinal temperature gradient; instead, the quality and quantity of benthic food resources and productivity may be responsible for the observed reproductive differences (Ituarte et al 2006;Bas et al 2007). Further, recent studies have demonstrated that burrows are places used for copulation, although differences in the form and size of the burrows between the two habitats promote differences in successful post-copulatory guarding behavior (Sal Moyano et al 2012). During the reproductive season, N. granulata individuals can spawn several batches of eggs (Ituarte et al 2004(Ituarte et al , 2006, although the extent of the receptive period was not assessed before the present study.…”
Section: Introductionmentioning
confidence: 96%
“…San Antonio Oeste (SAO) is a large intertidal area (143 km 2 ) placed in the western bank of San Antonio Bay and is characterized by extensive sand-cobble intertidal flats; Riacho San José (RSJ) is a smaller intertidal area (2 km 2 ) located in the southwestern extreme of San José Gulf; this is the southernmost population of this species registered so far. The life history, reproductive cycles and behavior of N. granulata in SAO are well known (ituarte et al 2006, Bas et al 2005, 2007, saL moyano et al 2012, Luppi et al 2013) but the population biology of this crab in RSJ has not been previously studied. These two sites have similar climatic and hydrographic characteristics: tidal amplitude and predictability, mean water temperature from November to April, a period that includes the whole reproductive season (Fig.…”
mentioning
confidence: 99%
“…The crabs inhabit the intertidal zone, both mud flats and salt marshes (areas densely vegetated with cord grasses). Individual animals dig burrows for protection because they are preyed upon by several species of seabirds (Bachmann and Martinez, 1999;Blanco and Carbonell, 2001;Berón et al, 2011;Copello and Favero, 2001;Spivak and Sánchez, 1992), for minimization of adverse environmental conditions (Luppi et al, 2013), and for reproductive activities (Sal Moyano et al, 2012). The current study was performed on the populations inhabiting the coastal inlets of Mar Chiquita (37°40′S) and San Antonio Oeste (40°48′S), Argentina (Fig.…”
Section: Materials and Methods Animals And Populationsmentioning
confidence: 99%